Legal Knowledge and its Relation to some Offensive Skills Ending with Shooting from Jumps and Lay-up Performance Among Secondary School Basketball Team Players - Zaid Abdulzahra Hamidi; Luay Jaleel Manshad (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Legal knowledge is a crucial aspect of sports, particularly basketball, as it guides and organizes skillful performance within correct framework of rules. A player's familiarity with rules of game helps avoid mistakes and improve performance quality, especially in offensive skills that require precision and speed of execution. This study aimed to identify relations between legal knowledge and performance of some offensive skills ending with shooting jumping shoot and lay-up shoot among secondary school basketball team players.  The researchers used descriptive approach with correlational relationships, as it was suitable for nature of problem. Sample was selected purposively from players of teams that qualified for semi-finals of school championship, totaling 40 players. A legal knowledge scale consisting of 75 items was applied, in addition to conducting skill performance tests for skills under investigation. Data were statistically analyzed using simple correlation coefficient (Pearson). Results showed a significant positive correlation between legal knowledge and performance of offensive skills ending with shooting, indicating that a higher level of legal knowledge among players contributes to improving their skill performance.  the researchers concluded that legal knowledge represents an important factor in developing skill performance in basketball, as it plays a role in guiding performance and reducing errors, recommended necessity of paying attention to this aspect within educational and training programs and conducting similar studies on different groups.